2015
DOI: 10.1371/journal.pone.0139514
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Ovaries from Pigs with High And Low Litter Size

Abstract: Litter size is one of the most important economic traits for pig production as it is directly related to the production efficiency. Litter size is affected by interactions between multiple genes and the environment. While recent studies have identified some genes associated with prolificacy in pigs, transcriptomic studies of specific genes affecting litter size in porcine ovaries are rare. In order to identify candidate genes associated with litter size in swine, we assessed gene expression differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 68 publications
(55 reference statements)
1
60
2
Order By: Relevance
“…Among them, cell parts and cells, binding and catalytic activity, metabolic processes, and cellular processes were predominant in each of the three main categories, respectively. These observations are consistent with previous studies regarding ovarian transcriptomes of goats (Ling et al., ; Miao et al., ; Wang et al., ; Zhao et al., ) and pigs (Zhang et al., ). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway significant enrichment analysis revealed that the DEGs participated in 331 pathways, of which 22 significantly enriched pathways were identified in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among them, cell parts and cells, binding and catalytic activity, metabolic processes, and cellular processes were predominant in each of the three main categories, respectively. These observations are consistent with previous studies regarding ovarian transcriptomes of goats (Ling et al., ; Miao et al., ; Wang et al., ; Zhao et al., ) and pigs (Zhang et al., ). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway significant enrichment analysis revealed that the DEGs participated in 331 pathways, of which 22 significantly enriched pathways were identified in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…were also significantly upregulated in prolific JTGs compared to non-prolific TBGs (Table 1). These genes were also significantly upregulated in other prolific breeds of goats and pigs (Miao et al, 2016;Zhang et al, 2015). HSD3B and STAR regulate hormone metabolism pathways and follicle development (Khan, Guillemette, Sirard, & Richard, 2015;Loureiro, Ereno, Favoreto, & Barros, 2016).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…To find the quantitative trait loci (QTL) and causal genes for these traits, several studies for linkages [11-13] and candidate genes ([14-17] have been conducted by using modern molecular information. Many of the major genes involved in the prolificacy of pig, such as ESR , FSHB , RBP4 , PRLR , MTNR1A , OPN , BMP families, and GDF9 genes have been characterized [18, 19]. Genetic studies have revealed an increasing number of associated QTLs and candidate genes involved in pig litter size [20-22].…”
Section: Introductionmentioning
confidence: 99%